2012
DOI: 10.1136/bmjqs-2010-048330
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk of medical errors using structural-equation modelling: a 6-month prospective cohort study

Abstract: The SEM model constructed in this study suggested that potential root causes (exogenous variables directly or indirectly connected to the outcome which are not affected by other variables) were years of nursing experience, feeling unskilled, job stressors and sleep disturbance, with estimated standardised total (direct and indirect) effects of -0.22, 0.21, 0.008 and 0.005, respectively. A prospective design path analysis using the SEM model for both direct and indirect effects enabled a statistical exploration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 31 publications
2
27
2
Order By: Relevance
“…Second, these results provide the first evidence of an association between depressive symptoms and perceptions of patient safety in UK hospital nurses. Only a limited number of studies have previously investigated this and have focused on number of perceived errors (Tanaka et al 2012, Saleh et al 2014. This study finds further support for a link between depressive symptoms and safety perceptions in nurses, suggesting this is also present in UK nurses.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Second, these results provide the first evidence of an association between depressive symptoms and perceptions of patient safety in UK hospital nurses. Only a limited number of studies have previously investigated this and have focused on number of perceived errors (Tanaka et al 2012, Saleh et al 2014. This study finds further support for a link between depressive symptoms and safety perceptions in nurses, suggesting this is also present in UK nurses.…”
Section: Discussionsupporting
confidence: 66%
“…Similarly to burnout, depressive symptoms in healthcare staff may have consequences for patient care such as a greater likelihood of cognitive failures and medical errors (Allan et al, 2014, West et al, 2006. However, there has been less research into the consequences of depressive symptoms than burnout and only two studies have investigated depressive symptoms and patient safety amongst nursing staff (Tanaka et al, 2012, Saleh et al, 2014.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Previous studies have found that insufficient clinical experience and poor operation skills are partly responsible for medical errors. 6 As in many countries, the process of training Chinese medical students does not include courses related to medical errors. This leads to young surgeons lacking experience in regard to avoiding medical errors at work.…”
Section: Dovepressmentioning
confidence: 99%
“…5 In fact, the causes of medical errors are complex; they include the negligence of medical staff, defective regulations within medical institutions, and excessive workloads. 6 And excessive fatigue from the defective working system had a further negative performance impairment in shift-work for medical staff. 7 On the whole, most medical errors are due to the system, and being system-related, should be fixed by improving the system itself and reducing the risk of errors by managing processes and practices.…”
Section: Introductionmentioning
confidence: 99%
“…The current study was carried out in order to redress that gap in our knowledge. It was guided by the fact that short-term longitudinal studies (e.g., around 6-months) have successfully examined developmental change, such as risks of medical errors (Tanaka et al, 2012) and the effects of workplace bullying on job satisfaction (Rodríguez-Muñoz et al, 2009). The current study was a short-term longitudinal investigation of the SWS hypothesis that social withdrawal syndrome contributes to Bulimia as indexed by Bulimic symptoms during early adolescence.…”
Section: Empirical Support For the Social Withdrawal Syndrome Hypothesismentioning
confidence: 99%